Comparison of the relative age effect between elite versus sub-elite level in youth football players - Breuer, J.; Jakobs, J.; Staub, I.; Vogt, T. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: The relative age effect (RAE) is a well-known phenomenon that has been observed in many sports. In this context, elite level football is amongst the fields of interest that have been studied frequently (Deprez et al., 2013). Thus, the level of competition is one of the factors affecting the RAE. Earlier studies showed that the RAE is more pronounced in higher competition levels, which is explained by an increase in selection pressure (Jackson & Comber, 2020). At the same time, elite academies have access to higher qualified coaches and extensive scientific resources regarding the selection of talents. For this reason, one would expect weaker RAE at elite level. To gain further sport specific insight, this study aims to compare the prevalence and magnitude of the RAE between elite and sub-elite level in youth football.